2022
DOI: 10.51624/szocszemle.2022.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Helyi gazdaságfejlesztési gyakorlatok és önkormányzati szerepek a vidéki hátrányos helyzetű térségekben : Elemzési szempontok és esetek

Abstract: Kutatásunkban helyi gazdaságfejlesztési (HGF) gyakorlatokat és a települési önkormányzatok fejlesztésekben betöltött szerepét vizsgáltuk a vidéki, hátrányos helyzetű térségekben. A nemzetközi és hazai szakirodalom feltérképezését követően kidolgoztunk egy helyi gazdaságfejlesztési gyakorlatok kvalitatív leírására és összehasonlítására alkalmas – 17 tényezőből és 36 altényezőből álló –, komplex elemzési szempontrendszert, melynek segítségével tanulmányunkban bemutatunk két magyarországi HGF gyakorlatot. A vizsg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…However, in a substantive, "embedded" economy, in addition to satisfying material (economic) needs, economic activities are always directed towards fulfilling social, protective, welfare, community, etc., functions (Defourny and Nyssens, 2017). On the one hand, by providing local employment and livelihoods, they can reduce outmigration, and on the other hand, some research has shown that they are beneficial for cooperation, joint innovative thinking and creativity (social renewal capacity), local identity and attachment (Csurg o and Megyesi, 2015;Steiner and Teasdale, 2017;Kiss and R acz, 2019;Kiss and R acz, 2022). Borzaga et al (2014) point out that meeting changing social needs encourages social economic actors to continuously grow and develop new products and services by exploiting previously unused resources, which can even appear as a competitive advantage in the Beyond the formal economy market.…”
Section: Motivation and Function Of Work And Productionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, in a substantive, "embedded" economy, in addition to satisfying material (economic) needs, economic activities are always directed towards fulfilling social, protective, welfare, community, etc., functions (Defourny and Nyssens, 2017). On the one hand, by providing local employment and livelihoods, they can reduce outmigration, and on the other hand, some research has shown that they are beneficial for cooperation, joint innovative thinking and creativity (social renewal capacity), local identity and attachment (Csurg o and Megyesi, 2015;Steiner and Teasdale, 2017;Kiss and R acz, 2019;Kiss and R acz, 2022). Borzaga et al (2014) point out that meeting changing social needs encourages social economic actors to continuously grow and develop new products and services by exploiting previously unused resources, which can even appear as a competitive advantage in the Beyond the formal economy market.…”
Section: Motivation and Function Of Work And Productionmentioning
confidence: 99%
“…A high degree of adaptability and flexibility is necessary for the survival of these organisations in an uncertain and resource-poor environment (Kibler et al, 2014;Kiss and R acz, 2022;Lang and Fink, 2019). Under such circumstances, social enterprises have adapted to operating by reusing social capital (Di Domenico et al, 2010;Sunley and Pinch, 2012).…”
Section: Embeddedness In Societymentioning
confidence: 99%
See 3 more Smart Citations